CubicA - Agriculture Advisory App: The right information, at the right time, to the right farmer - CGIAR Platform for Big Data in Agriculture (2019)
The team successfully completed four key stages: (i) Scoping including field work and user research, (ii) Design and Development of the recommender system, (iii) Deployment to 3000 smallholder farmers in Uganda, (iv) Testing and Evaluation confirming CubicA significantly increase the access to information by the farmers from 5 to 10%.